Essential Oils on Mixed Coccidia Vaccination and Infection in Broilers - Oviedo-Rondon, E.O.; Clemente-Hernandez, S.; Salvador, F.; Williams, Peter; Losa, Riccardo (International Journal of Poultry Science, 2006)
One trial was conducted to evaluate the effects of two specific essential oil (EO) blends in broilers infected with viable oocysts of mixed Eimeria spp. Eight treatments were evaluated which consisted of three controls, two unvaccinated treatments and three treatments vaccinated at day of hatch with Advent® coccidia vaccine. The three controls were: 1) Unmedicated-Uninfected (UU), 2) Unmedicated-Infected (UI), and 3) antibiotic plus ionophore (AI). The two unvaccinated treatments were fed diets supplemented with either Crina® POULTRY (CP) or Crina® ALTERNATE (CA) at 100 ppm. Cocci-vaccinated treatments included one group fed diets without feed additives (WFA), and two fed diets supplemented with the two EO products (CP and CA) at the same concentration. At 19 d of age, all birds except those in the UU control were infected with E. acervulina, E. maxima, and E. tenella. Lesion scores (LS) and oocyst counts (OC) were performed 7 d post-infection and anticoccidial indexes (ACI) were calculated. The non-cocci-vaccinated chickens fed the EO blend CA, and the cocci-vaccinated chickens fed WFA diets had similar feed conversion ratios to the UU broilers, 7 d post infection. The cocci-vaccinated chickens fed diets containing EO had lower relative BWG than the cocci vaccinated group fed WFA diets. The lowest OC was observed in vaccinated birds fed WFA diets. Under the conditions of this experiment, the dietary inclusion of EO blends may serve as an alternative to antibiotic and/or ionophores in mixed Eimeria spp. infections in non-cocci-vaccinated broilers, but no benefits of EO supplementation were observed for vaccinated broilers against coccidia.